ANALISIS STRATEGI PEMBELAJARAN DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN - Afifah, R Ulya; Sofyan Iskandar; Dias Marisa; Salma Indah Oktriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is motivated by the limited number of comprehensive studies comparing the effectiveness of various learning strategies in enhancing elementary students’ conceptual understanding. Previous research has predominantly focused on academic achievement, with less attention given to how learning strategies support deep understanding, especially at the early cognitive development stage that requires concrete and contextual approaches. The main objective of this research is to critically evaluate the effectiveness of learning strategies-particularly problem-based learning and multi-representation approaches-in improving students’ conceptual understanding. The research problem addressed is the low level of conceptual understanding due to the dominance of conventional methods. This study employs a literature review method, systematically analyzing relevant secondary sources, including journals, books, and official documents, using descriptive and critical content analysis techniques. The findings reveal that the application of problem-based learning and multi-representation approaches significantly enhances students’ critical thinking skills and conceptual understanding compared to conventional strategies. The researchers conclude that contextual, flexible, and student-centered learning strategies are essential for optimizing learning outcomes. Therefore, teachers are encouraged to adapt relevant strategies to meet students’ needs, ensuring more effective and meaningful learning processes in elementary education.